User-friendly novel method of geopolymer con-crete production mixes - Sabu, Akshay; Rajamane, Nirmalakumar (International Journal of Engineering and Technology, 2018)
Geopolymer is an inorganic polymer, which can perform as an effective binder in place of Portland cement. With this, the Geopolymer concrete has become highly Ecofriendly with very low carbon footprint. The GPC formulation at present utilises industrial waste materials like fly ash and GGBS, which are activated with well-proportioned alkaline liquid. At present the commercially available lye and Sodium Silicate solution are used to prepare alkaline liquid capable of initiating geopolymer reaction. It is noticed that the liquid system has limited shelf life by making field production of Geopolymer concrete mixes was a difficult one more over the liquid system and its ingredients are difficult to transport over longer distances. This has been the main obstacle for development of large-scale applications of GPC mixes on commercial basis. This issue was addressed in the present study by using solid activator in replacement of liquid solution. The solid activating system can be produced just before the preparation of fresh GPC mixes at anyway at any time. It is found that the mechanical strength (40 – 45Mpa) property was similar to the liquid activating GPC mixes. This new technique of production of GPC mixes using solid activators can be consider as the major breakthrough for commercialization / large scale field applications of Geopolymer technology.